THE POTENCY OF Mycale vansoesti SPONGE EXTRACT AND FRACTIONS FROM MANADO TUA ISLAND WATERS AGAINST THE GROWTH OF Staphylococcus aureus AND Escherichia coli - Komang Ayu May Widyani; Defny Wewengkang; Erladys Rumondor (UNIVERSITAS SAM RATULANGI, 2022)
Sponges are one of the coral reefs components that have the potential to produce secondary metabolites with antibacterial, antifungal, and anticancer properties that have not been widely used. This study aims to determine the antibacterial activity of the extract and fractions of Mycale vansoesti sponge obtained from Manado Tua Island waters against the growth of Staphylococcus aureus as Gram-positive representatives and Escherichia coli bacteria as Gram-negative representatives. Samples were extracted using the maceration method with 95% ethanol solvent and fractionated with the liquid-liquid method using 3 types of solvents with different polarities, namely n-hexane, chloroform, and methanol. Antibacterial activity test using the Kirby-Bauer disc diffusion method. The test results showed that ethanol extract, n-hexane fraction, chloroform fraction and methanol fraction from Mycale vansoesti sponge sample obtained from Manado Tua Island waters have antibacterial activity against Staphylococcus aureus and Escherichia coli with moderate bacterial inhibitory power.